Vertical Axis Wind Turbine-Flettner Rotor Integration as Hybrid Propulsion Power on a Model Ship - Ratono, Erfprins Azhar; Suwasono, Bagiyo; Winarno, Istiyo; Sutiyo, Sutiyo (International Journal of Marine Engineering Innovation and Research, 2024)
Natural energy is something that can be utilized as an alternative energy besides fossil fuel energy. Considering that the need for fossil fuel energy is decreasing, the purpose of this research is to propose a utilization of natural energy in the form of wind. The implication of the use of this alternative energy in the hybrid power function is that the integration of vertical axis wind turbines and Flettner rotors is chosen as the main driving energy of the model ship that fully utilizes wind energy. The performance evaluation stages in this experiment include design and simulation for the turbine-Flettner rotor, and trials on a model ship using a monohull type hull. The objective of this research is to obtain the optimum performance of the combined vertical-axis wind turbine-Fletner rotor in supporting hybrid propulsion power on a model ship. The power required by Flettner is 0.695 Watt and the turbine rotate at a minimum angular velocity of 40 rpm. The highest contribution of the Flettner rotor at ship service speed 1 knot and ship total resistance of 0.01 kN reached 26,20%.